Age Structural Model of Zika Virus - J. Lamwong; P. Pongsumpun (My University, 2018)
Zika virus is mosquito-borne flavivirus.It can be transmitted between human by bitting of Aedes mosquitoes.It can also transmit chikungunya, yellow fever and dengue disease.Zika virus can spread through mosquito to human, human to mosquito and human to human.In this paper, we account the age structure of zika virus patiens.We divide into two groups: human and mosquito.Age structure of human population is separated two groups: juvenile and adult human.Standard dynamical modeling method is used for analyzing the behaviors of solutions.The stability conditions for the disease free and endemic equilibrium states are considered by Routh-Hurwitz criteria.We simulate our model by using numerical method.The numerical simulations are showed to confirm the analytical results.
Keywords: Zika Virus; Mosquito-borne diseases and control